THE PARTNERSHIP OF BUSINESS AND EDUCATION SECTOR INSTITUTIONS IN THE PREPARATION OF HIGHLY QUALIFIED PERSONNEL FOR INDUSTRIAL ENTERPRISES - L. Borisoglebskaya; O. Khudyakova (Вестник университета)
The article considers the relevance of such forms of cooperation as a partnership between business and educational institutions. Describes the mechanisms of interaction of industrial enterprises with education organizations in the preparation of highly qualified personnel for industrial enterprises on the example of JSC «Aviaavtomatika» named after V. Tarasov.